2010
DOI: 10.1016/j.jcrs.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens power calculation: Clinical comparison of 2 optical biometry devices

Abstract: The OLCR biometry device provided precise and valid measurements and thus can be used for the preoperative examination of cataract patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 20 publications
5
45
0
8
Order By: Relevance
“…Our results reinforce earlier studies [10][11][12][13][14] reporting the strong agreement found between LENSTAR and IOLMaster in AL, average K, and IOL power. An exception is a recent study, 27 which reported less satisfactory average K agreement between IOLMaster and LENSTAR; the mean difference being 0.67 D, with 95% LoA given by (0.07, 1.20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results reinforce earlier studies [10][11][12][13][14] reporting the strong agreement found between LENSTAR and IOLMaster in AL, average K, and IOL power. An exception is a recent study, 27 which reported less satisfactory average K agreement between IOLMaster and LENSTAR; the mean difference being 0.67 D, with 95% LoA given by (0.07, 1.20).…”
Section: Discussionsupporting
confidence: 92%
“…9 Assessing method agreement can also be useful for evaluating the relative importance of instrument variation as a source of error for IOL power. Several studies [10][11][12][13][14] that look at LENSTAR-IOLMaster agreement in AL, anterior chamber depth (ACD), IOL power, K1, and K2 measurements of phakic eyes have been done. All suggest that measurements obtained from LENSTAR and IOLMaster strongly agree.…”
Section: Introductionmentioning
confidence: 99%
“…Keratometric measurements obtained with IOLMaster have been shown to have a high agreement with LENSTAR (Haag-Streit, Bern, Switzerland) [8][9][10][11], different AKR devices [12,13], manual keratometers [14], Galilei Dual Scheimpflug Analyzer (GDSA) (Ziemer Group, Port, Switzerland) [12], and the Sirius Scheimpflug/Placido photography-based topography system (CSO, Italy) [15]. However, other studies reported that the IOLMaster gives significantly steeper corneal power values than the manual keratometer, Pentacam, and certain automated keratometers [2,13,16,17].…”
Section: Discussionmentioning
confidence: 79%
“…When SRK II, Hoffer Q, and Haigis formulas were used for IOL power calculation the difference between the Lenstar and IOLMaster were within 0.5D in 96, 95, and 87% of measurements, respectively, and were not considered to be clinically significant [7]. In cataractous eyes, the mean differences in IOL power calculation using SRK II, SRK/T, Holladay, and Haigis formulas as evidenced by Rabsilber et al demonstrated an overall mean of 91.0% ± 2.2% of patients within ± 0.50 D [28]. In healthy subjects, differences of calculated IOL power based on the SRK/T formula ranged from 0.20 D to 0.34 D in 95% of observations, depending on AL of the eye as evidenced by Cruysberg and colleagues [8].…”
Section: Discussionmentioning
confidence: 95%
“…Considering difference in AL measurements between two Table 4 Summary of agreement between applanation ultrasound and the Lenstar for observer 2 *LoA=limits of agreement laser biometers the IOLMaster and the Lenstar LS 900®, an excellent agreement was found in both cataract [7,10,11,28] and healthy eyes [2,8,10]. However, the OLCR measurements differed from the PCLI measurements with mean differences of +0.026 mm [10], +0.01 mm [7], +0.00 mm [28], and -0.03 mm [11] in cataract eyes and +0.01 mm [2], +0.023 mm [10], +0.03 mm [8] in healthy eyes. These differences in AL measurements between two laser biometers were statistically significant, but clinical relevance of these differences was insignificant [7,8,10,11].…”
Section: Discussionmentioning
confidence: 99%